Contribuições de Paulo Freire e Walter Benjamin para uma análise do ensino de língua portuguesa no Currículo Paulista - Abitante, Aldo (2021)
The present work is a review about what is firmed in the Paulista Curriculum, it’s trying to realise the alienation of the word category and its linguistic prejudice, from the construction made based on Paulo Freire’s and Walter Benjamin’s theoretical reference – and also from some linguists who discuss the linguistic prejudice and the emancipatory practices of mother tongue teaching from Bagno’s, Brito’s, Geraldi’s, Lucchesi’s, Possenti’s, Rodrigues’ and Soares’ works. From the Benjamin's contributions to the word as authentic experience as well as Freire’s about the limit situation and education as dialogical praxis, make this question: how does the political-pedagogical proposal of São Paulo Curriculum for the teaching of Portuguese language hinder or favor the pronunciation of the authentic word by teachers and students? The study takes place through a qualitative research of documentary analysis, elaborated from the perspective of Critical Discourse Analysis to interpret its social context, the meanings and senses that it builds on the teaching of Portuguese language in its text. From what was raised in the study, it was understood that, despite the approximation of an enunciative-discursive theoretical basis, the current São Paulo Curriculum moves away from a critical emancipatory perspective of education, in the sense of facing neither the limit situations that alienate the word as an authentic experience, nor structural issues that fall on linguistic prejudice.